Do researchers in empirical ethics studies have a duty to act upon their findings?: case study in end-of-life decision making - Winkler, Eva C. (Journal of empirical research on human research ethics, 2019)
The outlined empirical study on the decision-making process concerning the limitation of life-prolonging treatment (DLT) in patients with advanced cancer at a University hospital setting triggered some new questions for research ethics with respect to studies using empirical methods in medical ethics. The analyzed data of the study showed that less than half of the patients were involved in DLT. Deciding against CPR (cardiopulmonary resuscitation) and transferal to the ICU (intensive care unit) without informing and explaining it to the perfectly competent patient can be regarded as a violation of the ethical principle of respect for autonomy. This is what the embedded researcher witnessed throughout the study recruitment and data acquisition, as the noninvolvement of patients was not just a result of the final data analysis. The ethical question raised in this situation was as follows: Does the embedded researcher has a moral duty to intervene when she witnesses that ethical standards are not upheld?
Gesehen am 20.12.2019